(untitled) (Bangladesh Journal of Medical Microbiology, 2018)
The primary clinical tool for predicting the lineage potential of leukemic blasts is the characterization of protein expression by immunophenotyping. It is common for acute leukemias to aberrantly express protein markers more typically associated with other lineages. Therefore, this study was designed to assess the frequency of aberrant antigens expression in childhood acute leukemia. Peripheral blood and bone marrow samples were collected from 76 clinically suspected and morphologically diagnosed untreated cases of acute leukemia (children of 0-<18 years). Flow cytometry immunophenotyping was carried out with the help of Flow cytometer (BD FACSVerse). Total 9 (11.84%) cases showed aberrant antigens expression. Out of 9 aberrantly expressed cases, 2 (22.22%) AML cases showed aberrant lymphoid marker CD7 expression. Co-expression of myeloid markers CD13 and CD117 found in 2 (22.22%) B-ALL cases and 2 (22.22%) cases of B-ALL expressed myeloid marker CD117. Myeloid marker CD33 expressed by 2 (22.22%) case of B-ALL. Only 1(11.11%) T-ALL case co expressed myeloid markers CD33 and CD117. These findings may help to recognize patients with high risk group and low remission rate as aberrant antigen expression may represent a poor prognostic indicator. Further studies are needed to confirm the correlation between aberrant phenotypes with prognosis and therapeutic response of acute leukemia. Bangladesh J Med Microbiol 2018; 12 (1): 10-14